Logic and its applications - Burke, Edmund; Foxley, Eric (New York : Prentice-Hall, 1996)
Providing a thorough introduction to logic programming, this new book covers both propositional and predicate logic with applications in circuit design, formal specification, and logic programming. Covers a formal approach to propositional logic, application to logic design, predicate logic, logic programming, formal system specifications and solutions. For professionals in the fields of computer science and mathematics.
1. Propositional Logic 2. Formal Approach to Propositional Logic 3. Applications to Logic Design 4. Predicate Logic 5. Logic Programming 6. Formal System Specification
Includes index.
Keywords: LOGIC PROGRAMMING